2003
DOI: 10.1088/0022-3727/36/7/317
|View full text |Cite
|
Sign up to set email alerts
|

Nanotribology and fractal analysis of ZnO thin films using scanning probe microscopy

Abstract: Characteristics of crystalline structure, roughness and nanotribology of ZnO thin films deposited under various power conditions were achieved by means of x-ray diffraction and scanning probe microscopy (SPM). The ZnO thin films were deposited on the silicon (100) substrates by a radio frequency magnetron sputtering system. Fractal analysis was derived from SPM images, to calculate the fractal dimension complexity of the surface geometry, via a substituting structure function. The results show that the roughne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…A different approach is the use of a relatively low-cost ZnO matrix, since it has been largely demonstrated its capacity to inhibit the growth of microorganisms, as well to act as a high-range antibacterial agent [9 ,10]. Furthermore, it´s possible to be obtained as thin films with high durability and enhanced mechanical properties [11,12]; as well as high transparency, which makes it ideally for glass-windows [13]. These properties makes ZnO attractive in places where high hygiene it´s necessary [14].…”
Section: Introductionmentioning
confidence: 99%
“…A different approach is the use of a relatively low-cost ZnO matrix, since it has been largely demonstrated its capacity to inhibit the growth of microorganisms, as well to act as a high-range antibacterial agent [9 ,10]. Furthermore, it´s possible to be obtained as thin films with high durability and enhanced mechanical properties [11,12]; as well as high transparency, which makes it ideally for glass-windows [13]. These properties makes ZnO attractive in places where high hygiene it´s necessary [14].…”
Section: Introductionmentioning
confidence: 99%
“…A promising approach to describe such self-similar state to the surface is the multifractal analysis [1][2][3]. Introduced by Benoit Mandelbrot, general pattern of geometric properties of the physical world, which is manifested in the self-similarity of its structure, has found numerous applications in materials science and has provided new opportunities for describing disordered materials microstructures using rigorous quantitative terms, such as fractal dimension.…”
mentioning
confidence: 99%
“…To date, it has been found that to describe the self-similarity of Corresponding author: Narek Margaryan, Ph.D., research fields: semiconductor phsics, nanotechnology, carbón films, quantum physics. natural materials is not enough just to use one of the fractal dimensions, and the works of different authors [1][2][3][4][5][6][7] show that the multifractal formalism provides such an opportunity. One of the important physical parameters of the nanostructured films is surface potential, which we can calculate using the results obtained by multifractal analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Modern nanoindentation testing equipment allows penetration depth curves to be measured as a function of load where the loads extend down to the range of micro-Newtons, resulting in typical penetration depths in the range of nanometers. This technique is well suited for examining the mechanical properties of thin films [9,10].…”
mentioning
confidence: 99%